“OTHER” AS THE FACTOR OF TRANSCENDENCE BEYOND THE “LIFE WORLD OF ORDINARY LIFE” - Морозов, А. Ю. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Such notions as “Ordinary life”, “Other”, “transcendence” are analyzed through the cultural transformations from premodernity to postmodernity.